1998
DOI: 10.1073/pnas.95.25.14944
|View full text |Cite
|
Sign up to set email alerts
|

Mature monocytic cells enter tissues and engraft

Abstract: The goal of this study was to identify the circulating cell that is the immediate precursor of tissue macrophages. ROSA 26 marrow mononuclear cells (containing the ␤-geo transgene that encodes ␤-galactosidase and neomycin resistance activities) were cultured in the presence of macrophage colony-stimulating factor and flt3 Ligand for 6 days to generate monocytic cells at all stages of maturation. Expanded monocyte cells (EMC), the immature (ER-MP12 ؉ ) and more mature (ER-MP20 ؉ ) subpopulations, were transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 42 publications
(24 reference statements)
1
65
0
Order By: Relevance
“…It has been generally believed that the blood-brain barrier (BBB) in the mature brain is largely impermeable to lysosomal enzymes, and that the CNS benefits observed in some patients with LSD receiving allogeneic BMT treatment early in life (Ͻ2 years old) may depend on diapedesis of donor HSC-derived macrophage/monocytes into the brain (33). Recently, a study performed on mice with another LSD, metachromatic leukodystrophy, showed that gene-marked HSCs overexpressing relatively high levels of the aryl sulfatase A enzyme (ARSA) were far more efficient at reversing the preexisting CNS deficits (demyelination) than BMT using normal HSCs (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally believed that the blood-brain barrier (BBB) in the mature brain is largely impermeable to lysosomal enzymes, and that the CNS benefits observed in some patients with LSD receiving allogeneic BMT treatment early in life (Ͻ2 years old) may depend on diapedesis of donor HSC-derived macrophage/monocytes into the brain (33). Recently, a study performed on mice with another LSD, metachromatic leukodystrophy, showed that gene-marked HSCs overexpressing relatively high levels of the aryl sulfatase A enzyme (ARSA) were far more efficient at reversing the preexisting CNS deficits (demyelination) than BMT using normal HSCs (34).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9-/-, CD18-/-, CD62ELP-/-or Rosa26βgeo mice (on a B6×129 genetic background), bred and housed at our facility, were used in some experiments; these mice were previously described. [8,9] For human HPC transplantation, NOD/SCIDβ2microglobulin-/-mice (NOD/SCIDβ2m-/-, Jackson Laboratories) were used as recipients. Mice were housed in the Specific Pathogen Free mouse vivarium of the Department of Comparative Medicine at the University of Washington, Seattle, WA, with autoclaved chow and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow, with defined sympathetic innervations is the site of hematopoiesis and is a primary source of circulating and tissue leukocytes (Bruno et al, 2001;Kennedy and Abkowitz, 1998;Lawson et al, 1992;Merad et al, 2002;Takahashi et al, 1996). Our previous work has demonstrated the association of critical trauma with sympathetic activation leading to the dynamic release of norepinephrine within the bone marrow (Jones et al, 1986;Tang et al, 2001;Tang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%